Fatores que influenciam o comportamento do consumidor de edificações sustentáveis: um estudo exploratório no contexto brasileiro - Kirby, Regiane Cristina Laveli de Souza (Universidade Federal de São Carlos, 2018)
The study of green buildings consumer behavior, despite its importance, has been a subject little explored in the academic literature. However, a better understanding of this matter can generate greater industry interest, and attract in investment and development of this type of construction and raise public/consumer awareness about the sustainable aspects of buildings, expanding their perception and willingness towards green buildings. Thus, this research aims to identify the factors that influence consumer behavior of green buildings in Brazil. Firstly, a series of systematic reviews of the literature were carried out on the factors influencing consumers and were then analyzed in the light of the classical theory of consumer behavior, represented here by the Decision Process model of Blackwell et al. (2005). This led to the composition of the theoretical model presented in this paper, from which empirical qualitative-quantitative research was developed. In the qualitative approach, focus group techniques were used for validation of the proposed model along with in-depth interviews with owners of green buildings certified by the Green Building Council Brazil. The quantitative method used is a survey with the same population referenced above. The information from the survey was analyzed using descriptive statistical analysis, hypothesis testing and a multivariate analysis. The results demonstrate the importance of the influence of factors such as family and personal conceptions, as well as price, sustainable characteristics of the property, sustainability confidence in this type of building, green certification and consumer perception that this acquisition can make a difference in society in which they live. This is a pioneer study in Brazil, due to its comprehensiveness and for identifying a broad range of factors that can influence consumer behaviour towards green buildings.
Factors which influence purchase of green buildings in Brazil
Keywords: Imóvel sustentável; Edificações sustentáveis; Fatores; Comportamento do consumidor; Green buildings; Sustainable housing; Factors; Consumer behaviour; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS; ENGENHARIAS::ENGENHARIA DE PRODUCAO